Correlative Analysis of Specific Compatibilization in Composites by Coupling in situ X-Ray Scattering and Mechanical Tensile Testing - Seidt, Britta; Samsoninkova, Valeria; Hanßke, Felix; Gjardy, André; Fratzl, Peter; Börner, Hans G.; Wagermaier, Wolfgang (Frontiers in Materials, 2020)
In this study, a bio-inspired hybrid material is investigated by in situ X-ray scattering experiments in combination with mechanical tensile testing. The material is composed of nanometer-sized spherical magnesium fluoride particles which are linked via material-specific peptide-poly(ethylene glycol) (PEG) conjugates to a semi-crystalline poly(ethylene oxide) (PEO) matrix. Mechanically relevant changes in crystal size and orientation in the PEO matrix are followed by wide angle X-ray scattering during the application of tensile stress. The amorphous phase of PEO is stabilized by the surface-engineered MgF2 nanoparticles, leading to increased Young´s modulus and tensile strength. Furthermore, small angle X-ray scattering experiments allowed the identification of a layer on the MgF2 particle surfaces, which increases in thickness with the conjugate amount and leads to suppression of the agglomeration of MgF2 nanoparticles. In conclusion, the use of selected peptide-PEG conjugates tailored to link MgF2 particles to a PEO matrix successfully mimics the biological principle of interface polymers and suggests new directions for material fabrication for bio-applications.